Effects of transcutaneous electrical phrenic nerve stimulation and transcutaneous electrical diaphragmatic stimulation: A protocol for a randomized, single-blind, crossover trial - Caroline Gomes Mól; Ricardo Kenji Nawa; Angélica Cristiane da Cruz Britto; Raquel Afonso Caserta Eid; Elaine Cristina de Campos; Leandro Teixeira Saraiva; Renato Fraga Righetti; Wellington Pereira Yamaguti (PLoS ONE, 2026)
Background Patients in the intensive care unit (ICU) are at high risk of developing respiratory muscle weakness, which may lead to prolonged mechanical ventilation and worsening clinical outcomes. Noninvasive neuromuscular electrical stimulation techniques, such as transcutaneous electrical phrenic nerve stimulation (TEPNS) and transcutaneous diaphragmatic electrical stimulation (TDES), offer potential therapeutic options for patients unable to generate voluntary active contractions. However, there is limited research directly comparing the effects of these modalities on diaphragmatic function. The primary objective of this study is to evaluate the effects of TEPNS and TDES on diaphragmatic function in healthy adults. Secondary objectives include assessing the safety, feasibility, and perceived discomfort associated with the application of each technique. Methods This study will be a bicentric, randomized, single-blind, crossover trial that will be conducted at two hospitals in São Paulo, Brazil. Healthy adults aged 18–60, with a BMI between 18.5 and 24.9 kg/m 2 , no history of respiratory diseases, and no contraindications for the proposed electrical stimulation modalities will be included. Diaphragm thickness, thickening fraction, and mobility will be assessed using ultrasound during tidal breathing. Participants will be randomly assigned to begin the intervention with one of two experimental conditions: (1) TEPNS protocol or (2) TDES protocol. In addition, data on the safety and feasibility of each electrical stimulation modalities will also be collected. Trial registration This protocol is registered at ClinicalTrials.gov under the number NCT06339632.